Comparative Analysis of MicroRNAs between Sporophyte and Gametophyte of Porphyra yezoensis. (26th September 2012) - He, Linwen; Huang, Aiyou; Shen, Songdong; Niu, Jianfeng; Wang, Guangce
Abstract : Porphyra yezoensis Ueda is an intertidal marine red algae that has received increasing attention as a model organism owing to its important role in biological research and the agronomic industry. The two generations of Porphyra yezoensis, the sporophyte and the gametophyte, have the same genome but show great differences in many aspects, including structural features, habitat, and gene expression. To identify miRNAs and their probable roles in P. yezoensis development, we constructed and sequenced libraries of small RNA from P. yezoensis sporophytes and gametophytes. The sequencing data were analyzed, and 14 miRNAs were identified, with only one common to these two samples. Our results show that P. yezoensis has a complex small RNA processing system containing novel miRNAs that have no identifiable homolog in other organisms. These miRNAs might have important regulatory roles in development of the different generations of P. yezoensis .